Effect of Al2O3nanoparticles on grain sizes and dielectric properties of BaFe1/2Nb1/2O3ceramics - C. Warangkanagool (2018)
In this research, the effect of Al2O3nanoparticles on grain size and dielectric properties of BaFe1/2Nb1/2O3(BFN) ceramics were investigated. The powder was prepared by the conventional mixed oxide method and calcined at 900-1200°C for 4h. The optimum temperature for calcinations the pure phase, was found to be about 1100°C. The calcined powders and Al2O3nanoparticles (0.5, 1 and 2 vol%) were ball milled with 1 wt% PVA in ethyl alcohol for 12 h using the same method as mentioned earlier. The slurry was dried, sieved and pressed into a disc shape and sintered at 1350°C for 4h with heating rate of 5°C/min. The microstructure was examined by scanning electron microscope (SEM). The dielectric constant and dielectric loss of BFN ceramics with 0, 0.5, 1 and 2 vol% Al2O3nanoparticles were measured at 1 kHz frequency at room temperature using LCR meter. The results show that, the average grain sizes of BFN ceramics were found to decrease with the addition of the Al2O3nanoparticles. The dielectric loss of BFN ceramics with Al2O3nanoparticles was decreased about 40-50% of pure BFN ceramics. Copyright © Taylor & Francis Group, LLC.